Posted by **Ali** on Thursday, December 3, 2009 at 11:14pm.

Why does this happen?

A=3 and b=2

A+b=c is the equation.

Multiplying both sides of the equation makes the equation a^2+2ab+b^2 which is equal to a^2+ab-ac=-ab-b^2+bc

Dividing by (a+b-c) we find a=-b or 3=-2

Why?

## Answer this Question

## Related Questions

- Math - 4(j)-7=9 Add 7 to both sides of the equation and you get 4 j = 16 Now ...
- MATH PLEASE CHECK IT!!2 - m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m...
- ALGEBRA - Select all the statements that can be used as steps to solve the ...
- Algebra - Select all the statements that can be used as steps to solve the ...
- Algebra - Solve each literal equations for the indicated variable D = C - s/n ( ...
- Math - Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + ...
- can someone help me with a question of an explanat - my question is for math, I ...
- math - Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find...
- algebra - solve each literal equation for the indicated variable linear equation...
- Find the sum of thuis question - Can someone find the sum for this equation ...